Perbaikan daya dukung tanah dasar lempung yang distabilisasi dengan additive kapur dan matos terhadap kualitas lama waktu pemeraman - Umar, Rizki Prinanda; Iswan, Iswan; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
The subgrade is the base surface for placement of other pavement parts.  The strength and durability as well as the thickness of the pavement construction layer depend on the properties and carrying capacity of this basic soil.  There are many types of soil, one of the basic types of soil that can be said to be bad for a construction is a soil with clay type. The soil samples used were taken from Sidorejo village, Sidomulyo district, South Lampung, then in this study the soil samples were mixed with matos and lime with variations of 5, 8, 10 and 12%.  After obtaining the highest CBR value, soil samples were immersed with the duration of 7, 14, 21, and 28 days to be tested again its CBR value.Soil in this study belongs to the group A-7-5, with LL values 74.112%, PL 35.44% and PI 38.669%.  The dry weight value (γd) and the optimum water content (ωopt) increased as the amount of lime content added to the sample.  In the CBR test, the highest increase of CBR value occurred on a 12% lime mixture variation of 21.5%.  While for CBR testing after curing without immersion, the highest CBR value is found on 28 days of curing duration of 45%.  The addition of lime and matos proved to increase the value of CBR and soil bearing capacity. Keywords : Clay Soil, CBR, Matos, Lime